Looking Ahead to the Political Future: Voting Behavior of Generation Z in General Elections in Kediri Regency - East Java - Purnawati, Laily; Qorib, Fathul; Nurhajati, Nunun (Jurnal Komunikasi Ikatan Sarjana Komunikasi Indonesia, 2025)
General elections are a crucial component of the democratic system, involving the participation of all eligible citizens. Generation Z, as one of the significant voter groups, attracts the attention of political parties due to their large number of votes. However, this generation often exhibits apathy and a lack of political knowledge. This study aims to analyze the voting behavior of Generation Z and the factors influencing it. The study employs in-depth interviews with 14 informants consisting of students, university students, and private-sector workers, as well as Focus Group Discussions (FGD) with 7 university students. The results indicate that initial voter conditions, such as economic background and previous experiences, mass media, and the characteristics of parties or candidates, significantly shape the political preferences of Generation Z. Social media emerges as the primary source of information, while experiences and discussions in academic environments enhance political participation. Emotional and rational factors also influence voting decisions, with emotions toward certain parties or candidates and rational analysis of received information playing critical roles. These findings underscore the importance of political education and media literacy in shaping informed and critical voters, contributing to the strengthening of democracy and the development of a more inclusive society in line with the Sustainable Development Goals (SDGs).